SURGICAL RISK ASSESSMENT IN PATIENTS WITH LIVER CIRRHOSIS – A LITERATURE REVIEW - Elina Merashka (Journal of IMAB)
Patients with chronic liver injury and liver cirrhosis develop disease-specific pathophysiological abnormalities. These specific findings compromise the functional activity of other organs and systems, leading to poor postoperative outcomes and increased morbidity and mortality rates in this population of patients. This requires a thorough analysis of the aforementioned pathophysiological abnormalities in order to optimize the patient's clinical condition in the preoperative period and to improve their perioperative performance status. The impaired physiological reserves in patients with liver cirrhosis necessitate a detailed assessment of the surgical risk in each specific patient. For this purpose, there are multiple classification and scoring systems for assessment – ​​Child-Pugh – Turcotte (CPT), Model of end-stage liver disease (MELD), Model of end-stage liver disease – Na (MELD – Na), Albumin – Bilirubin score (ALBI), each with specific indications for clinical use. This literature review on the topic examines the pathophysiological changes in patients with liver cirrhosis and the above-mentioned classification systems for risk assessment, as well as the advantages and disadvantages of each of them.